Edukasi Jajanan Sehat Menggunakan Media Kincir Angka terhadap Peningkatan Pengetahuan, Sikap dan Perilaku Siswa - Mihzaluna _ Frisky; Elsa Yolanda Tanjung; Intan Maulani Munthe; Sri Ulina; Nada Amirah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2025)
The consumption of unhealthy snacks among junior high school students remains a significant issue that can impact health, including digestive disorders, obesity, and non-communicable diseases. Interactive health education is necessary to raise students' awareness in selecting safe and nutritious snacks. This study aimed to examine the effect of healthy snack education using the